J/ψ production as a function of charged-particle multiplicity in p-Pb collisions at root √sNN=8.16 TeV - Acharya, Sreemukta; Angelov, Venelin; Arslandok, Mesut; Berdnikova, Anastasia; Danisch, Meike; Feuillard, Victor; Glässel, Peter; Kim, Jiyoung; Kim, Minjung; Köhler, Markus Konrad; Leardini, Lucia; López, Jorge; et al. (Journal of high energy physics, 2020)
Inclusive J/psi yields and average transverse momenta in p-Pb collisions at a center-of-mass energy per nucleon pairs root s(NN) = 8.16 TeV are measured as a function of the charged-particle pseudorapidity density with ALICE. The J/psi mesons are reconstructed at forward (2.03< y(cms) <3.53) and backward (-4.46< y(cms) < -2.96) center-of-mass rapidity in their dimuon decay channel while the charged-particle pseudorapidity density is measured around midrapidity. The J/psi yields at forward and backward rapidity normalized to their respective average values increase with the normalized charged-particle pseudorapidity density, the former showing a weaker increase than the latter. The normalized average transverse momenta at forward and backward rapidity manifest a steady increase from low to high charged-particle pseudorapidity density with a saturation beyond the average value.
Im Titel steht sNN unter dem Wurzelsymbol, "NN" ist dabei tiefgestellt
Gesehen am 12.02.2021
The ALICE Collaboration: S. Acharya, V. Anguelov, M. Arslandok, A. Berdnikova, M. Danisch, V.J.G. Feuillard, P. Glässel, J. Kim, M. Kim, M.K. Köhler, L. Leardini, J.A. Lopez, N. Martin, A. Ohlson, Y. Pachmayer, K. Reygers, R. Schicker, A. Schmah, M.O. Schmidt, J. Stachel, B. Windelband, A. Yuncu [und viele weitere]